Malignant Melanomas of the Skin Arising on the Feet - Bartoš, Vladimír; Kullová, Milada (Klinicka onkologie, 2018)
BACKGROUND: Cutaneous melanoma frequently develops on the lower limbs, but rarely on the feet, in people with light skin. By contrast, the feet are one of the most frequently affected sites in people with dark skin. This study assessed the prevalence and clinico-pathological findings of biopsy-proven skin melanomas that were diagnosed over 11 years. MATERIALS AND METHODS: The study group comprised 217 primary melanomas from 210 patients. RESULTS: Eight (3.7%) melanomas were located on the feet. These were all invasive and obtained from 8 patients (5 females and 3 males) aged 56-85 years (mean age 72 years). In general, the lesions were large (mean diameter 3.5cm) and had a high Breslow index (mean thickness 5.6mm). They were all ulcerated, and some invaded deep into the subcutaneous tissue. Histologic analyses demonstrated that three tumors exhibited features of acral lentiginous melanoma, two were nodular melanomas, and one was a superficial spreading melanoma. Two cases could not be histologically classified. CONCLUSION: Although skin melanomas arising on the feet are relatively rare in our ethnicity, they are usually bioptically diagnosed at an advanced stage. Such melanomas may initially imitate other pathologic entities. Therefore, this location should not be overlooked during the medical workup, and melanoma should be suspected when patients present with non-healing defects or local pigmented changes on the soles of the feet or toes. Key words: malignant melanoma - anatomic distribution - foot The authors declare they have no potential confl icts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 9. 2. 2018 Accepted: 16. 5. 2018.
Keywords: nádory kůže; Humans; Skin Neoplasms; lidé středního věku; Melanoma, Cutaneous Malignant; melanom; or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 9. 2. 2018 Accepted: 16. 5. 2018; Female; Aged; products; senioři; lidé; noha (od hlezna dolů); malignant melanoma - anatomic distribution - foot The authors declare they have no potential confl icts of interest concerning drugs; maligní melanom kůže; ženské pohlaví; Male; Middle Aged; Melanoma; Aged, 80 and over; Foot; senioři nad 80 let; mužské pohlaví